2001
DOI: 10.1088/0967-3334/22/2/306
|View full text |Cite
|
Sign up to set email alerts
|

Pulsatile electrical impedance response from cerebrally dead adult patients is not a reliable tool for detecting cerebral perfusion changes

Abstract: The original objective of this work was to verify the possibility of using electrical pulsatile cerebral impedance measurements as a diagnostic aid for assessing the brain-death condition in adults; a subordinate target was to validate a simple method for detecting perfusional changes in the brain. To this end, impedance signals were recorded, for a comparative study, from both live subjects and brain-dead patients, using a simple four-electrode arrangement. Rather unexpectedly, pulsatile transcephalic impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…An average (Fig. 4b) of 500 EKG pulses elucidates a 12% peak increase in blood flow, as well as a latency of 150ms between the R-peak and rCBF increase, consistent with previous studies (Montgomery et al, 1995; Basano et al, 2001). …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…An average (Fig. 4b) of 500 EKG pulses elucidates a 12% peak increase in blood flow, as well as a latency of 150ms between the R-peak and rCBF increase, consistent with previous studies (Montgomery et al, 1995; Basano et al, 2001). …”
Section: Resultssupporting
confidence: 89%
“…As predicted, the heartbeat strongly modulated the rCBF inferred from laser Doppler, with the main rCBF peak occurring 150ms following the R-peak in the QRS wave of the EKG, consistent with prior estimates of the vascular delay from the heart to the brain (Montgomery et al, 1995; Basano et al, 2001; Kucewicz et al, 2007). While latency time periods have been relatively consistent across studies, the direction and absolute size of the peak change from baseline is highly variable due to a number of reasons including measurement modality and location.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…With regard to REG II, most authors support the hypothesis that the impedance signals obtained in their experimental studies could be due (to a greater or lesser extent) to the scalp blood flow (Jacquy et al 1974, Weindling et al 1982, Jevning et al 1989. In this sense, the results obtained by Basano et al (2001) are significant, who found no significant differences between the REG II waveforms obtained from healthy subjects and those obtained from braindead patients, whose blood flow in the internal carotid artery was shown to be completely stopped with transcranial Doppler sonography. However, it must be noted that several authors have measured true brain pulsatile impedance using intracerebral electrodes both in humans (Laitinen 1968) and in animals (Bodo et al 2003).…”
Section: Introductionmentioning
confidence: 62%
“…This controversy led REG II configurations to be preferred to REG I, even though Basano et al [12] did not find any differences between the REG II signals registered from healthy subjects and those from patients with brain death diagnosis.…”
Section: Introductionmentioning
confidence: 99%